2017
DOI: 10.13189/ujer.2017.050210
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Time Attitude Scale: Adaptation into Turkish

Abstract: This research is aimed at examining the validity and reliability of the Turkish version of the Time Attitude Scale. Data were collected from 433 adolescents; 206 males and 227 females participated in the study. Confirmatory factor analysis performed to discover the structural validity of the scale. The internal consistency method was used for reliability analysis. Confirmatory factor analysis revealed a good fit to the data (X² = 724.42, DF = 390, RMSEA = .045, GFI = .90, CFI = .91, IFI = .91, NNFI = .90, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…The six-factor solution yielded better fit to the data than the competing models based on valence and time periods. This finding replicates results reported in other studies differing in language and culture (e.g., Alansari et al, 2013;Buhl & Lindner, 2009;Çelik et al, 2017;Chishima et al, 2019;Cole et la., 2017;Donati et al, 2019;Juriševič et al, 2017;Konowalczyk et al, 2018;Mello et al, 2016Mello et al, , 2019Şahin-Baltaci et al, 2017;Worrell et al, 2013Worrell et al, , 2020. The strength of coefficients is another highlight of the measure, as all but three items had coefficients higher than .65 on their latent variable.…”
Section: Psychometric Properties Of Aati-ta Scoressupporting
confidence: 92%
See 1 more Smart Citation
“…The six-factor solution yielded better fit to the data than the competing models based on valence and time periods. This finding replicates results reported in other studies differing in language and culture (e.g., Alansari et al, 2013;Buhl & Lindner, 2009;Çelik et al, 2017;Chishima et al, 2019;Cole et la., 2017;Donati et al, 2019;Juriševič et al, 2017;Konowalczyk et al, 2018;Mello et al, 2016Mello et al, , 2019Şahin-Baltaci et al, 2017;Worrell et al, 2013Worrell et al, , 2020. The strength of coefficients is another highlight of the measure, as all but three items had coefficients higher than .65 on their latent variable.…”
Section: Psychometric Properties Of Aati-ta Scoressupporting
confidence: 92%
“…Internal consistency estimates ≥ .70 have been consistently reported for five of the six AATI-TA scores, with future negative scores having lower estimates in some samples (Worrell et al, 2020). Additionally, evidence in support of the hypothesized six factor structure has been reported for samples from the United States (Mello et al, 2016;Worrell et al, 2013), Germany (Buhl & Lindner, 2009;Worrell et al, 2013), New Zealand (Alansari et al, 2013), the United Kingdom (Cole et al, 2017;, Turkey (Çelik et al, 2017;Şahin-Baltaci et al, 2017), Albania (Worrell et al, 2020), Nigeria (Mello et al, 2019), Italy (Donati et al, 2019;Worrell et al, 2020), and Japan (Chishima et al, 2019).…”
Section: The Adolescent and Adult Time Inventory -Time Attitudes Scalementioning
confidence: 88%
“…This structure has shown the best solution compared with a two-factor model focussing on valence (i.e., positive and negative) alone (e.g., Alansari et al, 2013; McKay et al, 2015; Mello et al, 2016; Şahin-Baltacı et al, 2017), and a three-factor model that represents the three time periods (i.e., past, present, and future; e.g., Alansari et al, 2013; McKay et al, 2015; Mello et al, 2016; Şahin-Baltacı et al, 2017; Worrell et al, 2013, 2018). Additionally, the six-factor structure has been confirmed in several countries, including Germany (Worrell et al, 2013), Japan (Chishima et al, 2017), and Turkey (Çelik et al, 2017; Şahin-Baltacı et al, 2017).…”
Section: The Psychometric Properties Of the Ati-tamentioning
confidence: 91%
“…Cronbach’s alpha coefficients have been found to range from 0.67–0.89 for the Past Positive subscale, from 0.720.90 for the Past Negative subscale, from 0.770.94 for the Present Positive subscale, from 0.72–0.91 for the Present Negative subscale, and from 0.770.93 for the Future Positive subscale. The reliability of the Future Negative subscale appeared to be the weakest, ranging from 0.53–0.89 (Alansari et al, 2013; Andretta et al, 2013; Çelik et al, 2017; Chishima et al, 2017; McKay et al, 2015; Mello et al, 2016; Prow, Worrell, Andretta, & Mello, 2016; Şahin-Baltacı et al, 2017; Worrell et al, 2013, 2018). Considering McDonald’s (1999) omega ( Ω ), a similar pattern of results has been obtained, with values equal to or above 0.80 for the ATI-TA subscales with a positive valence (Alansari et al, 2013; Chishima et al, 2017; McKay et al, 2015; Mello et al, 2016; Worrell et al, 2018), whereas somewhat lower values have been reported for the Past Negative ( Ω = 0.75), Present Negative ( Ω = 0.77) (Şahin-Baltacı et al, 2017), and the Future Negative subscale, for which Ω values ranged from 0.68–0.78 (McKay et al, 2015; Mello et al, 2016; Worrell et al, 2018), and for the Future Positive subscale, which Mello and colleagues (2016) found to be equal to 0.74 in the younger and 0.72 in the older adult sample.…”
Section: The Psychometric Properties Of the Ati-tamentioning
confidence: 99%
See 1 more Smart Citation